Pelatihan Pengolahan Data, Peningkatan Supply Response, dan Pelatihan Diversifikasi Produk pada KUB Yasinta Desa Sokawera Kecamatan Cilongok - Istiqomah Istiqomah; Arif Andri Wibowo (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2024)
KUB Yasinta was established in 2020 in response to the pandemic, which led to the cessation of entertainment activities such as party equipment rental, sound systems, music studio operations, and school music training programs. These circumstances promote the formation of a collaborative business group by bringing together ex-musicians and local residents to manufacture organic fertilizer. Currently, the business is diversifying its product range to twelve products, which are promoted to schools and distributed on consignment to retail stores. The first issue is that KUB Yasinta has been maintaining manual bookkeeping records; however, the data has not undergone any processing. Data processing is essential for enhancing performance as itÂ  allows to analyze the seasonality of sales, determine the best-selling products, and identify the outlets with the highest sales volume. Hence, the team arranged training sessions for data processing. The second issue arises from a deficient supply response due to the scarcity of production kitchen and equipment, for which, the team offered support to improve them. The third issue is to address the untapped local potential. The chairperson affirmed that marketing has not been a problem. However, the members' skills are confined to producing typical traditional products. Ä°n fact, there is local potentials such as fish and cow's milk. Therefore, the team arranged training sessions to produce shredded fish, fish crackers, and yogurt as innovative product alternatives. This project promotes knowledge and skills, increases product diversity, and increases KUB Yasinta's turnover.